Pediatric psoriasis and association with cardiovascular and metabolic comorbidities: Systematic review and meta‐analysis. Issue 4 (20th May 2020) - Phan, Kevin; Lee, Geoffrey; Fischer, Gayle
Abstract: Background/Objectives: There is an increasing volume of evidence which supports the link between psoriasis and cardiometabolic risk including obesity, metabolic syndrome, diabetes, hyperlipidemia, and myocardial infarction. Although one‐third to one‐half of psoriasis cases start during childhood, it is unclear whether childhood psoriasis is similarly associated with a cardiometabolic risk profile. Methods: Electronic database searches were performed to identify studies comparing the proportion of pediatric psoriasis cases with controls in terms of dichotomous outcomes including the proportion of patients with overweight BMI, obese BMI, metabolic syndrome, diabetes, hypertension, hyperlipidemia, ischemic heart disease, or heart failure; continuous outcomes recorded include BMI, systolic blood pressure, diastolic blood pressure, HDL, LDL, triglycerides, and total cholesterol. Results: A statistically significant association was found between pediatric psoriasis and overweight/obesity as well as waist:height ratio >0.5, in addition to metabolic syndrome, diabetes, hyperlipidemia, hypertension, and cardiac ischemia and failure. The association with obesity is dependent on the severity of disease, where moderate‐severe psoriasis patients have higher odds of obesity compared to mild psoriasis. Conclusions: Our systematic review and pooled meta‐analysis demonstrate a significant association between childhood psoriasis and obesity, central adiposity, and other cardiometabolic comorbidities. Clinicians should consider the assessment of comorbidities in children with psoriasis, which may allow for early lifestyle interventions and education.